Multiple sclerosis disease-modifying drug use by immigrants: a real-world study - Jonas Graf; Huah Shin Ng; Feng Zhu; Yinshan Zhao; José M. A. Wijnands; Charity Evans; John D. Fisk; Ruth Ann Marrie; Helen Tremlett (Scientific Reports, 2023)
Abstract Little is known about disease-modifying drug (DMD) initiation by immigrants with multiple sclerosis (MS) in countries with universal health coverage. We assessed the association between immigration status and DMD use within 5-years after the first MS-related healthcare encounter. Using health administrative data, we identified MS cases in British Columbia (BC), Canada. The index date was the first MS-related healthcare encounter (MS/demyelinating disease-related diagnosis or DMD prescription filled), and ranged from 01/January/1996 to 31/December/2012. Those included were ≥ 18 years old, BC residents for ≥ 1-year pre- and ≥ 5-years post-index date. Persons becoming permanent residents 1985–2012 were defined as immigrants, all others were long-term residents. The association between immigration status and any DMD prescription filled within 5-years post-index date (with the latest study end date being 31/December/2017) was assessed using logistic regression, reported as adjusted odds ratios (aORs) with 95% confidence intervals (CIs). We identified 8762 MS cases (522 were immigrants). Among immigrants of lower SES, odds of filling any DMD prescription were reduced, whereas they did not differ between immigrants and long-term residents across SES quintiles (aOR 0.96; 95%CI 0.78–1.19). Overall use (odds) of a first DMD within 5 years after the first MS-related encounter was associated with immigration status.